Interaction of triflupromazine with distearoylphosphatidylglycerol films studied by surface pressure isotherms and cyclic voltammetry at a 1,2-dichloroethane/water interface - Colqui Quiroga, Mónica Vanesa (2010)
The effect of triflupromazine (TFP) on molecular packing of distearoylphosphatidylglycerol (DSPG), adsorbed at the water/1,2-dichloroethane interface, was investigated using cyclic voltammetry (CV) and surface pressure-molecular area isotherm. TFP partition in the DSPG monolayer changes the structure of the film. The results indicate that a fluidizing effect, dependent on the time and the drug concentration, takes place leading to an increase in the permeability of the film. This effect is produced by TFP either from the organic or from the aqueous phase due to the amphiphilic nature of this drug. Nevertheless, the expansion of the film is enhanced when TFP acts from the aqueous phase